ПАРЕМИИ –КАК ЯСНЫЕ ИСТОЧНИКИ - Темирова Шоира Гайбуллаевна; Очилова Насиба Нематовна (Journal of new century innovations, 2023)
Аннотация: Данная работа раскрывает особенности паремий, так как в них запечатлен весь познавательный опыт народа, его морально-этические, социально-эстетические, художественные и воспитательные идеалы. / This work reveals the features of proverbs, as they capture the entire cognitive experience of the people, their moral, ethical, socio-aesthetic, artistic and educational ideals.